Proposta de indicadores para avaliação de desempenho dos sistemas de gestão ambiental e de segurança e saúde no trabalho de empresas do ramo de engenharia consultiva - Almeida, Clarissa Lima (2013)
The process of implementing a management system adds value to the organizational culture, since it develops skills which are related to activity-planning and executing, prioritizes teamwork ability and promotes the reliability of the production system. Thus, one of the main tools employed in the economic policy of organizations has been the implementation of an Environmental Management System (EMS). Moreover, the growing number of accidents broadcasted by the media has made organizations to seek in for Occupational Health and Safety Management Systems (OHSMS) an instrument to achieve better results in the field of OSH. The use of indicators of performance evaluation helps organizations quantify and report the performance of their management systems. Therefore, the aim of this study was to propose a set of performance evaluation for EMS and OHSMS a of a NBR ISO 14001:2004 and OHSAS 18001:2007 certified company, in order to improve the performance of these systems contributing to their continuous improvement processes. With this purpose, a case study in a consulting engineering company was conducted, where necessary data to enable the indicators proposal and development was raised, mainly through interviews, staff questionnaires application and the accompanying of audits carried out in the company. Thus, 23 indicators were proposed, 11 for EMS and 12 for OHSMS. The proposed indicators can be employed in EMS and OHSMS of companies of any industry, since they are indicators which can be easily implemented and controlled. Based on the obtained results, it was also observed the importance that employees have for the process of continuous improvement of management systems, from the action of measuring the level of knowledge they have on EMS and OHSMS, with the application of questionnaires. The results attained with this measurement at the consulting company showed that all organizational levels of this company (strategic, tactical and operational) showed satisfactory performance in the questionnaire solving